Techniques of video-assisted thoracoscopic surgery lobectomy and critical review of published data. (December 2016) - Andrews, Weston G; Paul, Subroto
Lung cancer resection techniques have gone through many changes and adaptations. Traditional thoracotomy provided sufficient visualization to fully resect the lobe as well as adequate lymph node dissection. Many thought that this allowed for the most accurate surgical staging of a lung cancer, but subjected the patient to longer hospital stays and increased morbidity and mortality. As with many major surgical operations there has been a culture shift toward minimally invasive techniques, but the adoption has been slow. We present the technique of video-assisted thoracoscopic surgery lobectomy and the literature supporting its use in the treatment of early-stage lung cancer.